B vitamins, homocysteine, and neurocognitive function in the elderly - Selhub, J; Bagley, L C; Miller, J; Rosenberg, I H (The American journal of clinical nutrition, 2000)
Evidence of the importance of the B vitamins folic acid, vitamin B-12, and vitamin B-6 for the well-being and normal function of the brain derives from data showing neurologic and psychologic dysfunction in vitamin deficiency states and in cases of congenital defects of one-carbon metabolism. The status of these vitamins is frequently inadequate in the elderly and recent studies have shown associations between loss of cognitive function or Alzheimer disease and inadequate B vitamin status. The question that arises is whether these B vitamin inadequacies contribute to such brain malfunctions or result from aging and disease. From a theoretical standpoint, these inadequacies could give rise to impairment of methylation reactions that are crucial to the health of brain tissue. In addition or perhaps instead, these inadequacies could result in hyperhomocysteinemia, a recently identified risk factor for occlusive vascular disease, stroke, and thrombosis, any of which may result in brain ischemia. Advances in the understanding of this putative relation between inadequate vitamin status and loss of cognitive function in the elderly are likely to be slow and may depend on the outcomes of both prospective studies and longitudinal studies in which nutritional intervention is provided before cognitive decline occurs.